O cômputo das dificuldades - Mitsi Pinheiro de Lacerda (EccoS – Revista Científica)
In this article I develop brief reflection on research in school daily life, trying to understand some of the traps that sometimes lead us to making speeches permeated by positivism logical. These traps crystallize the "look miss", materializing in texts that are thought sufficient and closed on several assignments of meaning. For that, I turn to the narratives of events in schools and dialogue with the theoretical, so try to understand the mechanisms that reduce such events. My option of understanding uses the propositions of Boaventura Santos when talks about the project of modernity and the contribution of Whitehead, when he speaks of the details present in the frequencies of life. I conclude by saying that the perception of other possibilities for what has been explained from a single point of view, is something that depends on the availability of the researcher to find them in small signs that commonly despised when we succumb to the simplistic speech.